2016
DOI: 10.1134/s1607672916030133
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of proteins of the vesicle cycle in dopaminergic neurons in modeling of Parkinson’s disease

Abstract: It is assumed that one of the causes of the degeneration of dopaminergic neurons is the dysregulation of the vesicle cycle, which is ensured by a number of proteins including syntaxin I, synaptotagmin I, complexins I and II, and Rab5. It was shown that there is a compensatory increase in gene expression of proteins responsible for exocytosis at the preclinical stage of Parkinson's disease (PD) in the in substantia nigra (SN) in mice. Conversely, in the model of the clinical stage of PD, the decreases of gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Upregulation of endosomal vesicle trafficking is also associated to Parkinson's disease where an increased RAB5 was found in the striatal neurons. 63 These evidences raised the hypothesis that a tight link between protein-compartment-marker and the vulnerability of cell types within selective brain regions exists. 42 …”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of endosomal vesicle trafficking is also associated to Parkinson's disease where an increased RAB5 was found in the striatal neurons. 63 These evidences raised the hypothesis that a tight link between protein-compartment-marker and the vulnerability of cell types within selective brain regions exists. 42 …”
Section: Introductionmentioning
confidence: 99%
“…Disorders of the synaptic vesicle cycle participate in the pathogenesis of PD and play a critical role in degeneration of dopaminergic neurons. Synaptotagmin-1 (SYT1), a potential target in treating nervous system disorders, regulates neuron exocytosis and the synaptic vesicle cycle ( Mingazov and Ugrumov, 2016 ; Liu and Kaeser, 2019 ). It has been demonstrated that by sponging miR-34-5p, overexpression of SYT1 has a neuroprotective effect in a mouse model of PD ( Shen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%